Anaesthetics and analgesics used in adult fish for research: A review. (August 2019) - Martins, Tânia; Valentim, Ana; Pereira, Nuno; Antunes, Luis Marques
The number of fish used in research has increased in the last decades. Anaesthesia is required when fish must be held immobile and it is crucial to promote fish welfare, because these vertebrates can show signs of stress and/or pain during handling, transport, tagging, sampling and invasive procedures. The use of an inadequate anaesthetic protocol can compromise not only the welfare of the fish, but also the reliability of the research results. Thus, the development of suitable anaesthetic regimes for each fish species is important. This article reviews the main anaesthetic and analgesic agents used in adult fish in a research setting.